2011
DOI: 10.1002/jsfa.4509
|View full text |Cite
|
Sign up to set email alerts
|

Environmental conditions affect semolina quality in durum wheat (Triticum turgidum ssp. durum L.) cultivars with different gluten strength and gluten protein composition

Abstract: Late sowings may represent a way of increasing pasta cooking quality whenever they place grain filling under thermal conditions able to increase protein percentage, although the accompanying decrease in yield may represent a drawback in environments prone to drought stress during ripening. The lower protein percentages of modern durum wheat cultivars under conventional sowing times results in a lower pasta cooking quality despite higher gluten strength.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
37
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 40 publications
(43 reference statements)
9
37
1
Order By: Relevance
“…Indeed, Sapirstein et al (2007) found a positive correlation between the extracted glutenin (50% propanol + DTT) and the alveographic parameters in durum wheat varieties. Also Fois et al (2011), evaluating by RP-HPLC the gluten extractable fractions, observed a higher gluten index consistent with a lower gliadin/glutenin ratio in cultivar Svevo with respect to old durum wheat genotypes. In addition, an increase in the glutenin sub-fractions expression (in particular B-type LMW-GS) in modern Italian durum wheat cultivars was recently observed (De Santis et al, 2017).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Indeed, Sapirstein et al (2007) found a positive correlation between the extracted glutenin (50% propanol + DTT) and the alveographic parameters in durum wheat varieties. Also Fois et al (2011), evaluating by RP-HPLC the gluten extractable fractions, observed a higher gluten index consistent with a lower gliadin/glutenin ratio in cultivar Svevo with respect to old durum wheat genotypes. In addition, an increase in the glutenin sub-fractions expression (in particular B-type LMW-GS) in modern Italian durum wheat cultivars was recently observed (De Santis et al, 2017).…”
Section: Discussionmentioning
confidence: 63%
“…In addition, the higher relative expression of the B-type LMW-GS in the modern durum wheat varieties has been recently reported by De Santis et al (2017). While the effect of breeding in terms of subunit composition was deeply investigated (De Vita et al, 2007;Ribeiro et al, 2016), lacking information is available on the changes in the proportion of the different protein fractions due to breeding activity (Juhasz et al, 2003), in particular on durum wheat (Fois et al, 2011). In order to deep insight into the changes in relative composition of grain protein fractions due to breeding activity during 20 th century, in this paper an old and a modern group of Italian …”
Section: Introductionmentioning
confidence: 98%
“…These authors also observed a decrease in GI when planting was delayed and proposed that temperatures higher than 30˚C during grain filling might affect the gluten polymerization process. In a similar study, GI increased as temperatures rose to 30˚C and then decreased under higher temperatures [25]. In addition, spaghetti cooked firmness and protein content were positively correlated, but independent of planting date.…”
Section: Introductionmentioning
confidence: 67%
“…It is known that in the L 48-35 region there is a higher concentration of LMW type 1 or 2 and of some LMW glutenins codified by GluB3 locus associated to the dough quality. In particular in the literature it is reported that both Ciccio and Svevo show the LMW-2 (Fois et al, 2011;Giuliani et al, 2012), which gives superior grain quality characteristics than the allelic group LMW-1.…”
Section: Resultsmentioning
confidence: 99%
“…Saint Pierre et al (2008) studying 9 wheat genotypes, found that the percentage of gliadins increased more rapidly than glutenins as flour protein increased; since maximum rate of synthesis of glutenins was reported to occur later than maximum rate of gliadins, the authors concluded that a late water stress could have more detrimental effect on the synthesis of glutenins than of gliadins. Also in durum wheat Fois et al (2011) reported that the ratio gliadins/glutenins decreased linearly as days after anthesis increased, being the synthesis of gliadins higher in the earlier stage of maturation, whereas glutenins accumulate more rapidly towards the latter stage.…”
Section: Introductionmentioning
confidence: 95%